Analysis of the Influence of Production Time Management and Quality Control Systems on the Operational Efficiency - Khairul Nisa; Tuti Anggraini; Marliyah Marliyah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This research is within the discourse of operational management, specifically related to the effectiveness of time management and quality control systems in culinary businesses. This study aims to analyze the influence of production time management and quality control systems on operational efficiency in Martabak SMEs. Bankka 99 in Stabat, Langkat. This study uses a quantitative approach with a cross-sectional design. Primary data were collected through distributing questionnaires to employees involved in production and quality control activities, with a sample of 30 respondents selected using a purposive sampling technique. The hypothesis tested is that production time management and quality control systems have a positive effect on operational efficiency. The analysis was carried out using multiple linear regression through SPSS. The results showed that both variables have a positive and significant effect on operational efficiency, with a simultaneous contribution of 73.3 percent. This finding reinforces the importance of time management and quality control systems as key elements in improving operational performance. Practically, this research contributes to traditional culinary SMEs in optimizing production processes to increase competitiveness and business sustainability